The Role of Customer Satisfaction in Mediating the Effect of Islamic Service Quality and Social Engineering on Customer Loyalty: Evidence from Bank Syariah Indonesia - Tati Atmayanti; Ade Kurnia (Lembaga Bale Literasi, 2026)
In keeping with the growing public recognition of the significance of Sharia-based financial transactions, the growth of Islamic banking in Indonesia, especially in the city of Mataram, exhibits a favorable trend. Bank Syariah Indonesia (BSI) KC Mataram, one of the top Islamic banks in the area, is essential to addressing the community's financial needs in accordance with Islamic values. Using customer pleasure as an intervening variable, this study attempts to examine the impact of social engineering and Islamic service quality on customer loyalty. In this study, 100 BSI KC Mataram clients were given a questionnaire as part of an associative quantitative approach, and the SEM-PLS model was used for data analysis. The analysis's intriguing conclusions show that social engineering significantly and favorably affects customer happiness. On the other hand, customer loyalty is directly impacted by the quality of Islamic services, even though it has little effect on satisfaction. Another research shows that customer satisfaction and social engineering both play a major role in the rise of loyalty. It's interesting to note that contentment, as an intervening variable, only effectively mediates the relationship between social engineering and loyalty; it has little effect on the association between loyalty and the caliber of Islamic services. This finding has significant ramifications for BSI KC Mataram's management since it shows that social engineering may be used to increase customer happiness and improve loyalty. In the meantime, loyalty can be directly impacted by the quality of Islamic services without first requiring a rise in satisfaction.